Knowledge of Dental Trauma and Orthodontic Management of Traumatized Teeth by a Group of Lithuanian Orthodontists - Simona Stučinskaitė; Paulina Laugalė; Dominyka Grinkevičienė; Rita Vėberienė; Dalia Smailienė (Medicina, 2023)
Background and Objectives. There is a deficiency of research on orthodontic movements and management strategies for traumatized teeth to avoid further treatment complications. The aim of the study was to evaluate the knowledge of Lithuanian orthodontists about dental trauma and the orthodontic management of traumatized teeth. Materials and Methods. Lithuanian orthodontists and orthodontic residents were introduced to the purpose, objectives and questionnaire of the study. The questionnaire was developed based on demographics, the participants’ personal experience, specific questions about dental traumas and orthodontic treatment tactics for patients with a history of dental trauma. Results. A total of 54 participants (42 orthodontists and 12 orthodontic residents) completed the survey. The overall response rate was 42.9%. The results of the survey revealed that the largest share of the study participants—61%—stated that they had treated traumatized teeth just a few times during the whole practice. Briefly, 53.7% of respondents inquired about the dental trauma history only if they saw signs of complications. The results of the survey revealed that the frequency of correct answers to questions about dental trauma was 63.7%, and that about the orthodontic treatment of traumatized teeth was 54.9%. It is worth noting that one-third of physicians pointed out the lack of information about the orthodontic management of traumatized teeth. Conclusion. The knowledge of Lithuanian orthodontists and orthodontic residents about dental injuries and the orthodontic treatment of traumatized teeth is insufficient. Further educational training is recommended.